Calculation of the Reactivity of Alkyl Ketene Dimer with Ethanol and the Characterization of Reaction Products - CHEN, FUSHAN; SONG, XIAOMING; LIU, FUSHENG; LIU, DANFENG (Asian Journal of Chemistry, 2014)
The structure of alkyl ketene dimer was built by Gauss view. Gaussian03 quantum chemistry packages were used for quantitative calculation of alkyl ketene dimer and alcohol. The DFT was chosen to optimize the ground state geometries by B3LYP basis set in the 6-311G(d,p) level. The Mulliken charge distribution, energy and frontier molecular orbital characteristics were calculated. It was shown that C(54) of lactone ring had a higher positive charge which was 0.411128 C. The frontier molecular orbital indicated that the activity of alkyl ketene dimer was mainly focused on the lactone ring. Ethanol was chosen to react with alkyl ketene dimer.The reaction products werecharacterized by FTIR, NMR and SEM.